Desarrollo de un modelo conceptual de la simulación numérica de un proyecto de inyección continua de vapor y un proyecto de inyección de aire en un campo de crudo pesado. (2022)
Nowadays, one of the most used tools by the petroleum engineer is numerical simulation through software, through which the validation of the data obtained in the well is carried out and it allows corroborating the information related to the exploitation and/or production of hydrocarbons, simulation is a modern discipline in reservoir engineering and an important tool for predicting the behavior of reservoirs under different exploitation schemes; There are currently different softwares on the market with varied functions and characteristics. This document focuses on the use of the simulation software called Computering Modeling Group CMG which, through the use of its sub-tools, will help to carry out the simulation. comparison between two different improved recovery scenarios for the extraction of heavy crude oil of 13.3 °API in certain basins, which will allow in the future to know the viability of exploitation and what type of recovery to implement to increase crude oil production, recovery methods EOR for which the simulation will be carried out correspond to air injection and steam injection, tertiary recovery methods used due to the possibility of obtaining higher recovery factors that are typical for the exploitation of heavy and extra-heavy crude oils, being the case of the conceptual model that is handled, because these methods use thermal energy measured before which the properties of extra-heavy crude oil are modified, such as its viscosity, also interacting with the rock/fluid system, creating favorable conditions for oil recovery, leading to a decrease in interfacial tension, oil swelling, modification of the favorable wettability or phase behavior. Knowing the results of the simulation in both scenarios, air injection and steam injection, according to their favorability, the results of the grid of the conceptual model will be replicated to the neighboring wells, the favorability of each of the wells will be additionally estimated using the conceptual model. tertiary recovery methods, by comparing production rates.